A new genus of long-horned caddisfly from the Amazon basin (Trichoptera: Leptoceridae: Grumichellini) - Holzenthal, Ralph W.; Pes, Ana Maria Oliveira (Zootaxa, 2004)
Amazonatolica hamadae, new genus, new species (Leptoceridae: Grumichellini), is described from the Amazon basin of Brazil. The adult male and female, larva, pupa and case are described and illustrated. The biology and habitat of the new species is unusual for members of its tribe in that it occurs attached to vegetation in acidic, lowland streams.